Redistribution of Meiotic Crossovers Along Wheat Chromosomes by Virus-Induced Gene Silencing - Raz, Amir; Dahan-Meir, Tal; Melamed-Bessudo, Cathy; Leshkowitz, Dena; Levy, Avraham A. (Frontiers in Plant Science, 2021)
Meiotic recombination is the main driver of genetic diversity in wheat breeding. The rate and location of crossover (CO) events are regulated by genetic and epigenetic factors. In wheat, most COs occur in subtelomeric regions but are rare in centromeric and pericentric areas. The aim of this work was to increase COs in both “hot” and “cold” chromosomal locations. We used Virus-Induced gene Silencing (VIGS) to downregulate the expression of recombination-suppressing genes XRCC2 and FANCM and of epigenetic maintenance genes MET1 and DDM1 during meiosis. VIGS suppresses genes in a dominant, transient and non-transgenic manner, which is convenient in wheat, a hard-to-transform polyploid. F1 hybrids of a cross between two tetraploid lines whose genome was fully sequenced (wild emmer and durum wheat), were infected with a VIGS vector ∼ 2 weeks before meiosis. Recombination was measured in F2 seedlings derived from F1-infected plants and non-infected controls. We found significant up and down-regulation of CO rates along subtelomeric regions as a result of silencing either MET1, DDM1 or XRCC2 during meiosis. In addition, we found up to 93% increase in COs in XRCC2-VIGS treatment in the pericentric regions of some chromosomes. Silencing FANCM showed no effect on CO. Overall, we show that CO distribution was affected by VIGS treatments rather than the total number of COs which did not change. We conclude that transient silencing of specific genes during meiosis can be used as a simple, fast and non-transgenic strategy to improve breeding abilities in specific chromosomal regions.